Studi Perubahan Warna dan Kekuatan Tarikan Eceng Gondok Hasil Pemutihan Menggunakan Hidrogen Peroksida - Muktaridha, Muktaridha; Irhami , Irhami; Ali, Syurkarni (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2024)
Water hyacinth is an aquatic plant often used as a craft product because it is attractive for its various positive properties but requires further handling, especially regarding its color. White is one of the most popular types, and the manufacturing process involves bleaching stages using chemical compounds such as hydrogen peroxide (H2O2). The use of H2O2 in the bleaching process still has consequences for the quality of the material, which becomes easily damaged, and the bleaching process, which involves the presence of sunlight or ultraviolet lamps, occurs more quickly. This research examines the relationship between the duration of soaking water hyacinth in H2O2 solution in the presence of direct light or in dark conditions on its color and tensile test strength. Based on the research results, the Hue, Saturation, and Value (HSV) color data increase the brightness based on saturation and value data. Tensile test capability testing carried out using the Universal Testing Machine (UTM) instrument showed that immersing water hyacinth in H2O2 for 4-8 minutes did not cause a significant change in tensile test capability, so it was still possible for various purposes as a raw material in the creative industry.